A Rare Case of Vaginal Enterobiasis: A rare case of vaginal enterobiasis - Singh, Meghna (Annals of Pathology and Laboratory Medicine, 2023)
Enterobius vermicularis, also known commonly as pinworm is the most common intestinal parasite particularly in children. It is a nematode which mainly inhabits the ileocaecal region of intestine but can be found throughout the gastrointestinal tract from stomach to anus. Ectopic enterobiasis is a rare entity with very few cases reported in literature. We report here a rare case of vaginal enterobiasis.